G339(P) Transition to consultant. (24th May 2017) - Race, H; Sen, C; Scott-Lang, C
Abstract : Introduction and Aims: To provide a course to prepare trainees for the non-clinical aspects of transition from trainee to consultant. Methods: We combined information on how to develop for a consultant role from a survey of paediatric consultants (response rate 80), focus groups of senior trainees and performance data from the START examination to devise a two day 'Transition to Consultant Course' (T2C). The data was consistent between consultants and trainees at identifying key areas of concern: business planning, lack of networking, increased responsibility, limited leadership and management experience and worries about educational supervision and mentoring. Our T2C course addressed these areas in small groups and lecture based teaching by both newly qualified and experienced consultants as well as providing the opportunity to shadow a hospital manager and consultant. Results: Pre and post-course feedback showed significant improvement in many consultant-level skills: leadership, management, quality improvement, clinical governance and educational supervision (p<0.05). Following the course trainees felt better prepared to become a consultant (p<0.05). There were also significant improvements in understanding what a consultant does day-to-day, having the professional skills required to become a consultant and feeling well prepared for consultant interviews (p<0.05). In addition, the course helped trainees to develop an action plan (p<0.05). Conclusion: Trainees reported the course to be inspiring, empowering and improved confidence.A course to develop non clinical skills around transition to consultant is highly valued by trainees.